ANALYSIS OF FATWA PUJANGGA SONG - Ahmad Fauzan Yusman; Jagar Lumban Toruan; Erfan Lubis (SENDRATASIK UNP, 2017)
This researchwas aimed to analyzing the Fatwa Pujangga song by Said Effendi. The songwas analyed from its structures. The design of the research was qualotative using the content analysis approach. Data were obtain from library study, transcription, and laboratorial analysis.The research resultshow that the has 5 antecedent phrases and 1 consequent phrase. In addition, it consist of 3 minor melodies. The melodies and verses in thesong are dominantly syllabic. Howover, some if themare neumatic. In the term of its verses, the song is included in melogenic category. The songconsists of main chords such as chord I (tonic), chord II (supertonic), chord III (median), chordIV (subdominant), chord V (dominant), chord VI (submedian), and chord VII (the leading note). Finally, the song has three cadence,the perfect authentic cadence, the authentic half cadence, and deceptive cadence.It is found that the meaning of the found in the refers to the humble idol who appreciates his fans by writing this song as asymbol of gratitude toward them even though at moment, he is at the top of his popularity.Keyword : Analisis, Struktur lagu, lagu Fatwa Pujangga.